1988
DOI: 10.2307/1478815
|View full text |Cite
|
Sign up to set email alerts
|

Body Composition and the Comparison of Measurement Techniques in Different Levels and Styles of Dancers

Abstract: The physical appearance required in dance, particularly in terms of body weight and fat, is often a demand that hovers over the aspiring and professional dancer's career (Vincent, 1979). This investigation was intended to measure various aspects of body composition in different types of dancers, as well as use various methods. Measurements of percent body fat and lean weight may serve as a means of quantifying appearance in dance so that dancers may be guided towards appropriate body composition goals. This ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
21
1

Year Published

1989
1989
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 19 publications
2
21
1
Order By: Relevance
“…These guidelines were based on several studies using various methods of body composition in university adult female dancers. However, the levels of fatness measured in the present study are in the middle to the upper range of the %BF values reported for dancers elsewhere (1,5,7,11,18,25,34), but one should bear in mind that these subjects were students in professional dance schools, being engaged in both ballet and modern dance activities. Professional dancers have characteristics that clearly differentiate them from dance students.…”
Section: Discussioncontrasting
confidence: 41%
See 2 more Smart Citations
“…These guidelines were based on several studies using various methods of body composition in university adult female dancers. However, the levels of fatness measured in the present study are in the middle to the upper range of the %BF values reported for dancers elsewhere (1,5,7,11,18,25,34), but one should bear in mind that these subjects were students in professional dance schools, being engaged in both ballet and modern dance activities. Professional dancers have characteristics that clearly differentiate them from dance students.…”
Section: Discussioncontrasting
confidence: 41%
“…Consequently, its use as a criterion method may have important limitations and could limit the validity of the developed equation. The measurement of skinfolds has also been used in previous studies for the body composition assessment of ballet dancers (1,7,11,25). The percentage of body fat was estimated either by the widely used Durnin and Womersley equation (13) or by the Sinning equation (30) specifically developed for young gymnasts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study’s subjects had the same characteristics (age, sex and racial, health and leanness status) with previous similar studies [ 2 , 9 , 10 ] and our results show analogue [ 11 ] and even lower [ 2 ] BF% values compared to dancers who were studied elsewhere.…”
Section: Discussionsupporting
confidence: 78%
“…The measurement of skinfolds has also been used in previous studies for the body composition assessment of ballet dancers [ 10 , 12 , 13 ]. It represents an indirect method for estimating the degree of body fatness easily, quickly, and inexpensively [ 14 ].…”
Section: Discussionmentioning
confidence: 99%